The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3389/fnagi.2023.1131536
|View full text |Cite
|
Sign up to set email alerts
|

Concise review: Current understanding of extracellular vesicles to treat neuropathic pain

Abstract: Extracellular vesicles (EVs) including exosomes are vesicular vesicles with phospholipid bilayer implicated in many cellular interactions and have the ability to transfer multiple types of cargo to cells. It has been found that EVs can package various molecules including proteins and nucleic acids (DNA, mRNA, and noncoding RNA). The discovery of EVs as carriers of proteins and various forms of RNA, such as microRNAs (miRNA) and long noncoding RNAs (lncRNA), has raised great interest in the field of drug delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 119 publications
0
2
0
Order By: Relevance
“…Exosomes are not only involved in the normal physiological mechanisms of pain but also contribute to the development of chronic pain [7,22,23]. Unraveling the intricate details of exosome formation, cargo modification, and release in various chronic pain conditions requires dedicated research efforts.…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…Exosomes are not only involved in the normal physiological mechanisms of pain but also contribute to the development of chronic pain [7,22,23]. Unraveling the intricate details of exosome formation, cargo modification, and release in various chronic pain conditions requires dedicated research efforts.…”
Section: Extracellular Vesicles (Evs)mentioning
confidence: 99%
“…Neuropathic pain is a type of chronic pain that occurs following an injury or disease in the peripheral nervous system [124], and appears to be related to neuroinflammation [125,126]. Various clinical studies have shown that exosomes can improve neuropathic pain by reducing proinflammatory cytokines, promoting vascular regeneration, promoting neuronal proliferation and function by axonal regrowth and Schwann cell activation [127,128], which contribute to providing a favorable microenvironment for peripheral nerve regeneration. Another pathology responsible for chronic inflammatory pain is osteoarthritis.…”
Section: Exosomesmentioning
confidence: 99%